Intraoperative testing of colorectal anastomosis and the incidence of anastomotic leak: A meta-analysis. Issue 47 (20th November 2020) - Kryzauskas, Marius; Bausys, Augustinas; Jakubauskas, Matas; Valciukiene, Jurate; Makunaite, Gabija; Jasiunas, Eugenijus; Bausys, Rimantas; Poskus, Eligijus; Strupas, Kestutis; Poskus, Tomas
Abstract: Background: AL remains one of the most threatening complications in colorectal surgery. Significant efforts are put to understand the pathophysiological mechanisms involved in the development of leakage and to create the strategies to prevent it. We aimed to determine whether intraoperative testing of mechanical integrity and perfusion of colorectal anastomosis could reduce the incidence of AL. Methods: A systematic review and meta-analysis of papers published before November 2019 on PubMed, Scopus, Web of Science, and Cochrane Library databases and comparing intraoperative testing of the colorectal anastomosis with standard care were conducted. Odds ratios (ORs) and 95% confidence interval (CIs) were used to assess the association between intraoperative testing and AL. Results: A total of 23 studies totaling 7115 patients were included. Pooled analysis revealed intraoperative tests, for integrity (OR 0.52, 95% CI 0.34–0.82, P  < .001) and perfusion (OR 0.40, 95% CI 0.22–0.752, P  < .001) of the lower gastrointestinal tract anastomoses are associated with significantly lower AL rate. Conclusions: Intraoperative testing for either integrity or perfusion of anastomoses both reduce the AL rate. Studies looking at the combination of these two testing methods of anastomosis, especially intraoperative endoscopy, and indocyanine green fluorescence angiography may be very promising to further reduction of the AL. Abstract : Supplemental Digital Content is available in the text